Adaptive control scheme of variable speed wind turbines for frequency support - Ontiveros, Leonardo Javier; Sarasua, Antonio Ernesto; Madrid Chirinos, Cindy (Institute of Advanced Engineering and Science, 2025)
Wind generation has experienced significant growth in power systems, due to the high availability of the primary resource and the maturity of its technology, which allows a fast control of active and reactive power. However, its main disadvantage is the lack of controllability over the primary resource. This leads to unwanted frequency oscillations that affect the power system security as wind penetration increases. This is due to the inertia of wind turbines is decoupled from the inertia of synchronous machines connected to the power system. Based on the aforementioned information, this paper analyses the state of the art of control strategies that allow wind turbines to participate in the frequency control of the power system. The main contribution of this work is the novel control strategy proposed, which implements a virtual synchronous machine controlled by an adaptive control system to enhance the transient response of the wind turbine. This scheme allows efficient management of the turbine's rotating reserve without the need to reduce its output power or use expensive energy storage systems. This solution is suitable for power systems with high wind penetration (above 20%). The validity of this proposal is demonstrated through dynamic simulations in a test system.